Hardening Concrete Exposed to Realistic Curing Temperature Regimes and Restraint Conditions: Advanced Testing and Design Methodology - Anja Estensen Klausen; Terje Kanstad; Øyvind Bjøntegaard (Advances in Materials Science and Engineering)
Early age cracking (EAC) is a well-known problem area when it comes to concrete structures. The driving forces behind EAC are thermal dilation and autogenous deformation, but EAC is also strongly dependent on material and geometrical properties such as hydration heat development, tensile strength, E-modulus, creep, cross-sectional dimensions, and degree of restraint. The current document contains a description of the EAC design methodology that is currently being implemented in Norway. The basis of the methodology is to define and describe the material properties of a given concrete through laboratory testing and succeeding model fitting. The obtained material parameters are then evaluated and calibrated by comparing (1) stress development measured in a Temperature-Stress Testing Machine with (2) stress development calculated by using the obtained material properties and various multiphysical EAC calculation approaches. Special consideration is given to the effect of realistic curing temperature regimes on the various material properties and consequently on the EAC.